Cuba Hunger Force: Women’s Bodies to the Rescue - Tomé, Patricia (Petits Propos Culinaires, 2014)
The article examines the role of food fantasy – induced by scarcity and hunger – in the 1998 novel by Daína Chaviano – part of a series entitled The Hidden Havana–El hombre, la hembra y el hambre (The Man, the Female, and the Hunger) which won the prestigious Azorín prize that same year partly due to its personal recounting of a heroic young Cuban woman who – unlike the author herself who fled Cuba in – must live on the island at the cusp of the most pervasive national scarcity since the triumph of the socialist Revolution: the nineties. With a plot meant to awaken the sexual and culinary appetite of any reader, the erotic imagery begins to dissipate as the novel enters the realm of a socio-economic, political, and cultural snare. Amid a visually scrawny and disintegrating society, gastronomical images are peculiarly abundant in literary, cinema topographic, and musical productions written in and about the Cuba of the 1990’s. Food – obtaining it, cooking it, consuming it, and digesting it – becomes the sort of incentive a prototypical superhero (or heroine, as in our case) aims to obtain in order to heighten his or her powers – supernatural powers that will allow subsistence in a reality where ‘meat is gold for the poor.’